KONSEP PENDIDIKAN KARAKTER (TELAAH KITAB AYYUHAL WALAD KARYA AL-GHAZALI) - Khoir, Fatihul (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
Character education is very important in facing the current modern era, that is because currently there are many people around us who no longer care about character education, especially for today's young generation. Therefore, this study aims to find out how the concept of character education is in Al-Ghazali's book Ayyuhal Walad. So that later can be applied in everyday life. The research method used is a qualitative method, namely collecting primary and secondary data related to the theme of the discussion.The results of this study are that there are 3 concepts of character education that have been formulated by Al-Ghazali namely: 1) the priority of education, the essence of the priority of this education is that it is very important. Someone who has gained knowledge, then should be able to practice this knowledge in everyday life. 2) teacher characteristics, Al-Ghazali's words in the book imply that the deeds, behavior, morals and personality of a teacher are more important than the knowledge possessed. 3) student characteristics, there are 3 things that need to be considered by a student, namely the right intention in seeking knowledge, making the best use of time so that it is not wasted and practicing the knowledge that has been obtained.